Tibial Cut Accuracy in Mechanically Aligned Total Knee Arthroplasty Using Extensor Hallucis Longus Tendon to Determine Extramedullary Tibial Guide Position - Besa, Pablo; Vega, Rafael; Ledermann, Gerardo; Calvo, Claudio; Angulo, Manuela; Lira, María Jesús; Vidal, Catalina; Orrego, Mario; Irribarra, Luis; Espinosa, Julio; Vial, Raimundo; Irarrázaval, Sebastián (The Journal of Knee Surgery, 2021)
This study aimed to determine the tibial cut (TC) accuracy using extensor hallucis longus (EHL) tendon as an anatomical landmark to position the total knee arthroplasty (TKA) extramedullary tibial guide (EMTG), and its impact on the TKA mechanical alignment (MA). We retrospectively studied 96 TKA, performed by a single surgeon, using a femoral tailored intramedullary guide technique. Seventeen were prior to the use of the EHL and 79 used the EHL tendon to position the EMTG. We analyzed preoperative and postoperative standing total lower extremity radiographs to determine the tibial component angle (TCA) and the correction in MA, comparing pre-EHL use and post-EHL technique incorporation. Mean TCA was 88.89 degrees and postoperative MA was neutral in 81% of patients. Pre- and postoperative MAs were not correlated. As a conclusion of this study, using the EHL provides a safe and easy way to determine the position of EMTG.
Keywords: total knee arthroplasty; alignment; extramedullary guide; extensor hallucis longus tendon; anatomical landmark